Tinjauan Pelaksanaan Coding Diagnosa Dan Tindakan Pada Implementasi Rekam Medis Elektronik Puskemas Botania - Riska Pradita; Monadia (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
One of the activities in administering electronic medical records is coding diagnoses and medical procedures. Coding is the activity of providing clinical classification codes based on the international classification of diseases and medical procedures ICD 10, ICPC, and ICD 9-CM. The implementation of coding in electronic medical records also provides very significant changes because providing the correct code has the potential to impact the income of the Community Health Center. In carrying out coding, coding of medical actions is not carried out based on the ICD-9CM classification and codefication standards for medical actions. Apart from that, in accessing electronic medical records there is only one account used by all levels of the Health profession at the Botania Health Center, so it is feared that just anyone can change the contents of the electronic medical record. Based on this description, the researcher aims to conduct a review regarding coding challenges in the implementation of Electronic Medical Records, so that Community Health Centers can increase the accuracy and completeness of diagnosis and action codes. This type of research is a qualitative analysis with a cross-sectional design that reviews the challenges in coding electronic medical records. Data collection used observation, interviews and document study methods. The results of this research show that coding of medical actions in Electronic Medical Records does not comply with ICD-9 CM standards. The challenges include Man's needs not being in line with his qualifications, and also not understanding the system. In the method aspect, there is no SOP Coding as a standard for implementing coding in electronic medical records. Regarding the machine aspect, the features of the electronic medical record system are not complete according to standards and coding requirements. An unstable network that does not guarantee secure access to electronic medical record data is a challenge for Community Health Centers related to material aspects, as well as related to the money aspect for the costs of developing electronic medical records.